SARS-CoV-2, myocardial injury and inflammation: insights from a large clinical and autopsy study - Dal Ferro, Matteo; Bussani, Rossana; Paldino, Alessia; Nuzzi, Vincenzo; Collesi, Chiara; Zentilin, Lorena; Schneider, Edoardo; Correa, Ricardo; Silvestri, Furio; Zacchigna, Serena; Giacca, Mauro; Metra, Marco; et al. (Clinical research in cardiology, 2021)
Objective Despite growing evidence about myocardial injury in hospitalized COronaVIrus Disease 2019 (COVID-19) patients, the mechanism behind this injury is only poorly understood and little is known about its association with SARS-CoV-2-mediated myocarditis. Furthermore, definite evidence of the presence and role of SARS-CoV-2 in cardiomyocytes in the clinical scenario is still lacking. Methods We histologically characterized myocardial tissue of 40 patients deceased with severe SARS-CoV-2 infection during the first wave of the pandemic. Clinical data were also recorded and analyzed. In case of findings supportive of myocardial inflammation, histological analysis was complemented by RT-PCR and immunohistochemistry for SARS-CoV-2 viral antigens and in situ RNA hybridization for the detection of viral genomes. Results Both chronic and acute myocardial damage was invariably present, correlating with the age and comorbidities of our population. Myocarditis of overt entity was found in one case (2.5%). SARS-CoV-2 genome was not found in the cardiomyocytes of the patient with myocarditis, while it was focally and negligibly present in cardiomyocytes of patients with known viral persistence in the lungs and no signs of myocardial inflammation. The presence of myocardial injury was not associated with myocardial inflammatory infiltrates. Conclusions In this autopsy cohort of COVID-19 patients, myocarditis is rarely found and not associated with SARS-CoV-2 presence in cardiomyocytes. Chronic and acute forms of myocardial damage are constantly found and correlate with the severity of COVID-19 disease and pre-existing comorbidities. Graphic abstract